A Fast Visual Recognition Memory System in Humans Identified Using Intracerebral ERP. (10th December 2019) - Despouy, Elodie; Curot, Jonathan; Deudon, Martin; Gardy, Ludovic; Denuelle, Marie; Sol, Jean-Christophe; Lotterie, Jean-Albert; Valton, Luc; Barbeau, Emmanuel J
Abstract: One key item of information retrieved when surveying our visual world is whether or not objects are familiar. However, there is no consensus on the respective roles of medial temporal lobe structures, particularly the perirhinal cortex (PRC) and hippocampus. We considered whether the PRC could support a fast recognition memory system independently from the hippocampus. We recorded the intracerebral electroencephalograph activity of epileptic patients while they were performing a fast visual recognition memory task, constraining them to use their quickest strategy. We performed event-related potential (ERP) and classification analyses. The PRC was, by far, the earliest region involved in recognition memory. This activity occurred before the first behavioral responses and was found to be related to reaction times, unlike the hippocampus. Single-trial analyses showed that decoding power was equivalent in the PRC and hippocampus but occurred much earlier in the PRC. A critical finding was that recognition memory-related activity occurred in different frontal and parietal regions, including the supplementary motor area, before the hippocampus. These results, based on ERP analyses, suggest that the human brain is equipped with a fast recognition memory system, which may bypass the hippocampus and in which the PRC plays a critical role.